2013
DOI: 10.1111/jgh.12276
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic steatosis and severity‐related factors in obese children

Abstract: Non-alcoholic fatty liver disease is common in the obese pediatric population in our geographical area. High levels of ALT are associated with severe steatosis, although having ALT above the normal range is not common. Also, the lack of severity of steatosis can be predicted in a subgroup of children with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 36 publications
2
13
0
8
Order By: Relevance
“…Given the broad confidence interval found, the association may or may not have clinical impact and it should be taken with caution. These findings were also demonstrated in a similar study by Navarro-Jarabo, et al [20], where a higher level of triglycerides and higher BMI were related to hepatic steatosis. In addition to this, we looked more closely at children with moderate to severe steatosis by US and we found that HDLC was lower in this group of patients, which can be related to insulin resistance [21].…”
Section: Discussionsupporting
confidence: 83%
“…Given the broad confidence interval found, the association may or may not have clinical impact and it should be taken with caution. These findings were also demonstrated in a similar study by Navarro-Jarabo, et al [20], where a higher level of triglycerides and higher BMI were related to hepatic steatosis. In addition to this, we looked more closely at children with moderate to severe steatosis by US and we found that HDLC was lower in this group of patients, which can be related to insulin resistance [21].…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of the steatotic liver is rapidly increasing worldwide reaching almost 30% of the total population in some countries [1], [2], with incidences rapidly rising in the pediatric population [3]. Hepatic steatosis is largely considered the hepatic manifestation of the metabolic syndrome [4], although, in fact, recent studies have shown that it actually precedes the development of metabolic syndrome [5] and its prevalence is expected to rise along with the number of overweight and obese people [6].…”
Section: Liver Transplantsmentioning
confidence: 99%
“…Therefore, the risk factors associated with steatosis in obese children should be identified, especially for the most severe forms of steatosis. Our research group has recently shown that steatosis can be detected by Insulin resistance and the metabolic syndrome are related to the severity of steatosis in the pediatric population with obesity ultrasonography in 34% of children who are overweight or obese (14). The study also showed that the group of patients without steatosis and the group with mild steatosis had similar characteristics.…”
Section: Introductionmentioning
confidence: 72%
“…The study was performed in a subgroup of obese children from a cohort of a previous study that were referred to a childhood obesity unit (14). Glucose homeostasis and MetS characteristics were analyzed to determine the factors associated with severe steatosis confirmed by ultrasonography.…”
Section: Methodsmentioning
confidence: 99%